2011
DOI: 10.1002/iroh.201011314
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Macrophyte Breakdown, Associated Plant Chemistry, and Macroinvertebrates in a Wastewater Dominated Stream

Abstract: Replacement of native macrophyte species with exotic or invasive ones affects the quality of detritus entering streams and can alter nutrient cycles and community structure in aquatic ecosystems. Decomposition of air-dried native hardstem bulrush (Schoenoplectus acutus), invasive southern cattail (Typha domingensis), and exotic common reed (Phragmites australis) were studied in an urban stream (Las Vegas, Nevada, USA) using litter bags. Samples were analyzed for dry mass, lignin, nutrients, trace elements, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…For example, investigations at reach scale (Beisel et al, 1998;Peeters et al, 2004), clearly revealed the importance of depth, substrate and hydraulic conditions (Reice, 1980;Schmera & Eros, 2004; Barnes et al, 2013), food availability (Beisel et al, 2000) and biotic factors (Kelly et al, 2003;Nelson, 2011). Conversely, over larger scales, latitudinal gradients and variability in land-use/land-cover and bedrock geology appear to exert stronger influence and thus mask local scale effects (Allan, 2004;Mykrä et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For example, investigations at reach scale (Beisel et al, 1998;Peeters et al, 2004), clearly revealed the importance of depth, substrate and hydraulic conditions (Reice, 1980;Schmera & Eros, 2004; Barnes et al, 2013), food availability (Beisel et al, 2000) and biotic factors (Kelly et al, 2003;Nelson, 2011). Conversely, over larger scales, latitudinal gradients and variability in land-use/land-cover and bedrock geology appear to exert stronger influence and thus mask local scale effects (Allan, 2004;Mykrä et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Macrophytes are key components of aquatic systems (Thomaz et al, 2008), since they are the main source of autochthonous detritus in these systems (Pieczn´ska, 1993) and their decomposition is an important source of carbon, nitrogen and phosphorous, principally in small lakes (Nelson, 2011). These plants are often used by invertebrates as refuge for reproduction and protection against predators (Harrison et al, 2005;Ferreiro et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, macrophytes serve both as a direct food source (vegetal tissue, principally during decomposition) and indirect food source (substrate for development of periphyton) for invertebrates (Newman, 1991;Nelson, 2011). Invertebrates form an important link between the energy stored in detritus and the higher trophic levels of the aquatic food web (Gessner et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Each mesocosm enclosed a known stand of S. acutus or T. angustifolia. These two species were used because they possess different lignin content and decay characteristics (e.g., Nelson, 2011), and were common at the study site. Four mesocosms received eight approximately bi-weekly additions of N and P (~3.5 29 gN/m 2 and ~3 g P/m 2 , as controlled-release isobutylidenediurea fertilizer and K 2 HPO 4 ) during…”
mentioning
confidence: 99%